Scribal composition: Malachi as a test case - Lear, Sheree (Forschungen zur Religion und Literatur des Alten und Neuen Testaments, 2017)
Title Page -- Copyright -- Table of Contents -- Acknowledgments -- Abbreviations -- Chapter 1: Introduction -- 1.1 Introduction -- 1.2 What is a Scribe? -- 1.3 What is Scribal Composition? -- 1.4 Why Malachi? -- 1.5 Thesis -- 1.6 Goals of this Study -- Chapter 2: Malachi 2:10â16 -- 2.1 Introduction -- 2.2 Malachi 2:10â16 Translation -- 2.3 Commentary by Verses -- 2.4 Summary Graph of Reused Texts -- 2.5 Synopsis of the overarching argument of Mal 2:10â16 -- 2.6 Summary of Scribal Composition in Malachi 2:10â16 -- Chapter 3: Wordplay in Malachi -- 3.1 Introduction -- 3.2 Formatting of evidence -- 3.3 Phonological Wordplay -- 3.4 Graphic Wordplay -- 3.5 Semantic Wordplay -- 3.6 Wordplay Conclusions -- Chapter 4: Phinehas, he is Elijah -- 4.1 Introduction -- 4.2 Previous Scholarship -- 4.3 Literary Device: Literary Allusion -- 4.4 Malachi 2:4â7: The Ideal Levite -- 4.5 Malachiâs Motivation -- 4.6 Later Jewish Literature -- 4.7 Conclusions -- Chapter 5: Conclusion -- 5.1 Introduction -- 5.2 The Historical Scribe -- 5.3 Literary Production: Composition by the Scribes -- 5.4 Further research -- 5.5 Conclusion -- Appendix A -- 1. The Use of Deuteronomy in Malachi 2:1â2: -- 2. Establishing Reuse -- 3. How the Composer of Malachi Read Deuteronomy -- Appendix B: The Use of Genesis 31â33 in Malachi -- Bibliography -- Index of Subjects